If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + -2 + 4 + -2x = 40 Reorder the terms: -2 + 4 + 3x + -2x = 40 Combine like terms: -2 + 4 = 2 2 + 3x + -2x = 40 Combine like terms: 3x + -2x = 1x 2 + 1x = 40 Solving 2 + 1x = 40 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2' to each side of the equation. 2 + -2 + 1x = 40 + -2 Combine like terms: 2 + -2 = 0 0 + 1x = 40 + -2 1x = 40 + -2 Combine like terms: 40 + -2 = 38 1x = 38 Divide each side by '1'. x = 38 Simplifying x = 38
| -8p+-3p=-3p+-16 | | msquared+7=71 | | 1/3x=9.9 | | Y=(x-6)(x-(3+2i))(x-(3-2i)) | | 8x-6-5x=4-2x+8 | | 2+-2r=2+-6r | | 15(x+5)=3(5x+4)+63 | | 3x+3+x=x+4 | | 5w-18=27 | | 2+2r=2+6r | | 5-6+a-2= | | 4/5x=250 | | c-7=-3+2c | | 2+6n=4+4n | | 8x-8=-1+8x | | w=1/6ha | | -8x+3=-61 | | c=8*3.14*G | | 3200+200x-3x^2=0 | | 8x-(3x+7)-3=0 | | 3x^2-200x-3200=0 | | -5y^2-26y+160=0 | | .06*(x+8)=.03*(2x+9)+0.21 | | X*2Y=20 | | -2+5=3x-10 | | 0.014x^2+0.89=0 | | 3c+12=3 | | -5=5-2k | | -n+2x-4-9n-9x-8= | | 1,4=-t/6.5 | | 8=x^2-5x+8 | | 0=16x^2-3+2x |